2016
DOI: 10.1113/jp273327
|View full text |Cite
|
Sign up to set email alerts
|

Differences in TRPC3 and TRPC6 channels assembly in mesenteric vascular smooth muscle cells in essential hypertension

Abstract: Increased vascular tone in essential hypertension involves a sustained rise in total peripheral resistance. A model has been proposed in which the combination of membrane depolarization and higher L-type Ca channel activity generates augmented Ca influx into vascular smooth muscle cells (VSMCs), contraction and vasoconstriction. The search for culprit ion channels responsible for membrane depolarization has provided several candidates, including members of the canonical transient receptor potential (TRPC) fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…Measurement of oxidants and antioxidants in the aorta showed that this may be attributable to elevated SOD activity and reduced catalase activity leading to greater production of hydrogen peroxide and decreased catalase-mediated conversion of hydrogen peroxide to water (Uddin et al, 2003b). Different expression of canonical transient receptor potential (TRPC) 3 channels and of hetero-multimeric TRPC channels may also contribute to differences in vascular tone in the BPH/2 mice (Alvarez-Miguel et al, 2017).…”
Section: Heart Vessel and Kidney Structure And Functionmentioning
confidence: 99%
“…Measurement of oxidants and antioxidants in the aorta showed that this may be attributable to elevated SOD activity and reduced catalase activity leading to greater production of hydrogen peroxide and decreased catalase-mediated conversion of hydrogen peroxide to water (Uddin et al, 2003b). Different expression of canonical transient receptor potential (TRPC) 3 channels and of hetero-multimeric TRPC channels may also contribute to differences in vascular tone in the BPH/2 mice (Alvarez-Miguel et al, 2017).…”
Section: Heart Vessel and Kidney Structure And Functionmentioning
confidence: 99%
“…Osteoclast function might rely on an equilibrium between TRPC3 and TRPC6, leading to bone loss in mice lacking TRPC6. Recent studies showed discrepancies regarding expression and functional contribution of these channels [23,24], which may be related to the fact that the contribution of TRPC3 and TRPC6 channels depends on their association as homo-or heterotetrameric complexes and differences in their association pattern may change their function [25].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Bae et al [72] showed that the TRPC6 expression was enhanced in the mesenteric artery of DOCA-salt hypertensive rats, suggesting that aldosterone evoked TRPC6 upregulation, receptor-operated Ca 2+ entry (ROCE) and consequently hypertension development. [62][63][64]. They are involved in agonist-induced Ca 2+ increase and vasomotion in arteries from SHRs [64].…”
Section: Systemic Hypertensionmentioning
confidence: 99%